Seasonal hyporheic dynamics control coupled microbiology and geochemistry in Colorado River sediments. Issue 12 (3rd December 2016) - Danczak, Robert E.; Sawyer, Audrey H.; Williams, Kenneth H.; Stegen, James C.; Hobson, Chad; Wilkins, Michael J.
Abstract: Riverbed microbial communities play an oversized role in many watershed ecosystem functions, including the processing of organic carbon, cycling of nitrogen, and alterations to metal mobility. The structure and activity of microbial assemblages depend in part on geochemical conditions set by river‐groundwater exchange or hyporheic exchange. To assess how seasonal changes in river‐groundwater mixing affect these populations in a snowmelt‐dominated fluvial system, vertical sediment and pore water profiles were sampled at three time points at one location in the hyporheic zone of the Colorado River and analyzed by using geochemical measurements, 16S rRNA gene sequencing, and ecological modeling. Oxic river water penetrated deepest into the subsurface during peak river discharge, while under base flow conditions, anoxic groundwater dominated shallower depths. Over a 70 cm thick interval, riverbed sediments were therefore exposed to seasonally fluctuating redox conditions and hosted microbial populations statistically different from those at both shallower and deeper locations. Additionally, microbial populations within this zone were shown to be the most dynamic across sampling time points, underlining the critical role that hyporheic mixing plays in constraining microbial abundances. Given such mixing effects, we anticipate that future changes in river discharge in mountainous, semiarid western U.S. watersheds may affect microbial community structure and function in riverbed environments, with potential implications for biogeochemical processes in riparian regions. Key Points: Hyporheic zone expands and contracts with seasonal snowmelt cycle At depths where groundwater influence fluctuates, the microbial community is unique River‐groundwater mixing is the main control on microbial community structure